Ground cover vegetation of litchi orchards in relation to land use intensity in mountainous Northern Thailand - Dirk Euler (2018)
In mountainous northern Thailand, former swidden farming systems have become increasingly transformed into permanent agricultural land, which is mainly used for litchi (Litchi chinensis Sonn., Sapindaceae) cultivation. Plant species composition of the ground cover vegetation of litchi orchards was analyzed in the vicinity of two Hmong villages (Chiang Mai Province) implementing land use at different intensities. From the 49 litchi orchards (148 relevés) studied, a total of 275 plant species (predominantly annual pioneers) was recorded. Two major groups of orchard vegetation were separated by TWINSPAN classification, which corresponded with the sites related to the two villages. Further paired subdivisions were mainly related to the proportions of exotic and native species and life form composition among the species with the highest positive fidelity values. The differences between groups can largely be explained by factors of land use intensity and management, such as the duration of cultivation and the frequency of herbicide use and mowing. Knowledge on the relationships between management and composition of the ground cover vegetation in litchi orchards may contribute to the identification of appropriate strategies to promote ecological sustainability of land use in mountainous northern Thailand. © 2006 Asian Network for Scientific Information.